ΔJ = 2 Staggering in Rotational Bands of Diatomic Molecules - Bonatsos, Dennis; Daskaloyannis, C.; Drenska, S. B.; Lalazissis, G. A.; Minkov, N.; Raychev, P. P.; Roussev, R. P. (HNPS Advances in Nuclear Physics, 2019)
It is shown that the recently observed ΔJ = 2 staggering seen in superdeformed nuclear bands is also occurring in rotational bands of diatomic molecules